Potential of Kedabu (Sonneratia ovata Backer) Fruit Juice Supplemented in Kombucha Beverage as Antibacterial Agent - Nasution, Musyirna Rahmah; Nabilah, Clara; Djohari, Meiriza; Nurhapipah, Nurhapipah (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Riau Province has abundant natural resources of mangrove forests almost along the coast of Riau. Mangrove fruit can be developed into various processed foods, but processed foods derived from mangroves have not been widely developed and are of interest to coastal communities. Kombucha tea is a probiotic beverage produced through the fermentation of tea and sugar using a kombucha starter known as SCOBY (Symbiotic Culture of Bacteria and Yeast). The presence of sugar in kombucha colonies is a vital source of nutrition. Additionally, fruit juice can be incorporated to create variations of kombucha tea. Kedabu fruit (Sonneratia ovata B.), a native fruit of Riau Province, is recognized for its high carbohydrate content and secondary metabolites, which exhibit potential antibacterial properties. This research developed four formulations of kombucha tea, each with different concentrations of kedabu fruit juice (0%, 10%, 20%, and 30%). The study’s objectives were to formulate, evaluate the physicochemical properties and antibacterial activity of these formulations against Escherichia coli and Staphylococcus aureus. The organoleptic properties, alcohol content, pH, %TTA (Total Acidity Titratable), total LAB (Lactic Acid Bacteria), and yeast count were assessed during a 14-day fermentation period. The assay results indicated that the kombucha fruit kedabu tea formulation exhibited favorable organoleptic characteristics, a decrease in pH, an increase in %TTA, total LAB, and yeast count within the acceptable range defined by standards. Moreover, it displayed inhibitory activity against Escherichia coli and Staphylococcus aureus bacteria, falling within the weak to moderate categories.